Bit Error Rate Analytical Approach For Different Modulation Techniques Based On Comparison Of Conventional And Wavelet Based OFDM LTE Mechanisms (International Journal of Engineering and Computer Science, 2015)
Orthogonal Frequency Division Multiplexing is considered as an advanced communication model which haswide range of applications such as 3G, 4G, and Wi-Fi etc. Comparing with Frequency Division Multiplexing(FDM), we are providing a higher level of spectral efficiency by using the OFDM Multiple Carriers. Toovercome the problems of the Inter carrier interference (ICI) and inter symbol interference (ISI), using of thecyclic prefix which uses the available bandwidth of 20% for the loss of the Orthogonality between the subcarriers in OFDM. Providing of better Orthogonality which is based on the wavelet of OFDM and improvingof BER (Bit Error Rate) is also used in it. Increasing of the spectral efficiency we don’t require the cyclicprefix which is based on the wavelet system. In the upcoming of the 4th generation LTE, using of wavelets inplace of Discrete Fourier Transform (DFT) based OFDM is proposed. Using of the wavelets and DFT basedOFDM Systems we have compared the performance of the BER.